2019
DOI: 10.1177/0907568218824389
|View full text |Cite
|
Sign up to set email alerts
|

‘I can only be properly myself when I’m with her’: Early adolescent intra-ethnic immigrant group friendships as a safe space for identity exploration, negotiation and validation

Abstract: Intra-ethnic adolescent friendships can provide a safe space for the development of a sense of identity and belonging and this study explores the intra-ethnic friendship experiences of fifteen 11- to 12-year olds with non-Irish heritage in Ireland. The incorporation of principles and practices from expressive arts psychotherapy into creative focus groups and journaling within the governing framework of Dahlberg et al.’s reflective lifeworld approach provides different sensory pathways designed to optimise part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 53 publications
(56 reference statements)
1
3
0
2
Order By: Relevance
“…This confirms other studies showing that pupils who feel stigmatized feel more secure in intra-ethnic friendships (e.g. Hoare, 2019).…”
Section: Resultssupporting
confidence: 91%
“…This confirms other studies showing that pupils who feel stigmatized feel more secure in intra-ethnic friendships (e.g. Hoare, 2019).…”
Section: Resultssupporting
confidence: 91%
“…Þegar sérstaklega er litið til hóps ungra innflytjenda hefur komið í ljós að þeir saekja frekar til annarra innflytjenda eftir stuðningi til að takast á við áskoranir og streitu (Kim o.fl., 2012). Hoare (2019) komst einnig að því í rannsókn sinni að tengsl við vini af sama uppruna sköpuðu öruggt rými til sjálfsmyndarleitar, gagnkvaems stuðnings, skilnings og viðurkenningar. Svo virðist sem gott traust ríki við þessar aðstaeður og hlýtur að teljast eðlilegt að einstaklingar saeki aðstoð til þeirra sem eiga sér sambaerilegan reynsluheim og eru líklegri en aðrir til að sýna skilning á aðstaeðum viðkomandi.…”
Section: Vinatengsl Og Stuðningur Vinaunclassified
“…Góð tengsl við vini og önnur félagsleg tengsl unglinga af erlendum uppruna eru þýðingarmikil (Thomas og Choi, 2006). Traust vinatengsl baeta líðan og veita stuðning en geta einnig verið eins konar lykill að nýju samfélagi og tengslaneti til framtíðar (Hoare, 2019;Kim o.fl., 2012). Í þessu efni er ekki síður mikilvaegt að tengsl myndist milli unglinga af ólíkum uppruna til að auka víðsýni og samkennd í fjölbreyttu samfélagi og tryggja taekifaeri til EYRÚN MARÍA RÚNARSDÓTTIR virkrar þátttöku og áhrifa allra (Titzmann o.fl., 2015).…”
Section: Markmið Og Rannsóknarspurningarunclassified
See 1 more Smart Citation
“…Unlike their majority peers, Turkish and Moroccan minority adolescents see the ethnic culture of their immigrant families and communities as compatible with the (Belgian or Dutch) national culture of the majority society (Hillekens, Baysu & Phalet, 2019; Van Acker & Vanbeselaere, 2012; Verkuyten & Thijs, 2002). Likewise, qualitative findings showed that minority friends explored and co‐constructed multiple identities during adolescence together, suggesting that sympathetic minority friends enable the integration of ethnic and national identities (Hoare, 2019). Therefore, we expected that ethnic and national identification would be more compatible (i.e., less negatively associated or dissociated) in classrooms with more minority peers (relative group size) than in classes with fewer minority peers (Hypothesis 2).…”
Section: Introductionmentioning
confidence: 99%